Joseph Smith Fowler papers - Fowler, Joseph Smith, 1820-1902.
Correspondence, writings, memorandum book, biographical material, printed matter, and other papers relating chiefly to Fowler's political activities as a Unionist and to his service as comptroller of the treasury of Tennessee during the Civil War and as U.S. senator from Tennessee during Reconstruction. Subjects include Reconstruction and the impeachment of President Andrew Johnson.
Microfilm edition available
Microfilm produced from originals in the Manuscript Division.
Educator, lawyer, and U.S. senator from Tennessee.
Collection material in English.
Finding aid available in the Library of Congress Manuscript Reading Room and at
Material transferred from the Ethan Allen Hitchcock papers in 1942.
Keywords: Johnson, Andrew, -- 1808-1875 -- Impeachment; Tennessee. -- Comptroller of the Treasury; Reconstruction (U.S. history, 1865-1877); Unionists (United States Civil War); Tennessee -- History -- Civil War, 1861-1865.; United States -- History -- Civil War, 1861-1865.; United States -- Politics and government -- 1865-1900.; Educators; Lawyers; Senators, U.S. Congress -- Tennessee